2005
DOI: 10.1086/502530
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Multiple Endemic Strains of Methicillin-ResistantStaphylococcus aureusin a Nursing Home: An 8-Year Study

Abstract: PFGE was performed on residents' first clinical MRSA isolate (n=94) during 8 years. Sixty-one percent of the isolates were clustered in time (P < .05) and space (P < .05) (i.e., 2 separate statistically significant tests). Isolates from individual units were genetically related, with only the occasional unrelated isolate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…On the other hand, a case of MRSA infection may follow a prolonged period of asymptomatic nasal colonization after an aspiration event or development of a necrotic wound. 115 Outbreaks in LTCFs accounted for a substantial proportion (15%) of reported epidemics 116 (Table 1). Clustering of URIs, diarrhea, skin and soft tissue infection, conjunctivitis, and antibiotic-resistant bacteriuria have been noted.…”
Section: Epidemic Infections In the Ltcfmentioning
confidence: 99%
“…On the other hand, a case of MRSA infection may follow a prolonged period of asymptomatic nasal colonization after an aspiration event or development of a necrotic wound. 115 Outbreaks in LTCFs accounted for a substantial proportion (15%) of reported epidemics 116 (Table 1). Clustering of URIs, diarrhea, skin and soft tissue infection, conjunctivitis, and antibiotic-resistant bacteriuria have been noted.…”
Section: Epidemic Infections In the Ltcfmentioning
confidence: 99%
“…There have been case reports of not only vancomycin tolerance but also vancomycin resistance (3). This has an impact on the healthy population, with the growing incidence of communityacquired MRSA, and is of even more concern for the evergrowing number of elderly patients with numerous comorbid conditions, including hospitalized and nursing home patients (4,6,7,17). Numerous alternative regimens are being tested in this era of multidrug-resistant organisms.…”
mentioning
confidence: 99%
“…However, there have been a few studies reporting the dynamics of MRSA over long periods of time (3,18,19,41,42,45,51). These studies showed that the molecular epidemiology of MRSA is evolving.…”
mentioning
confidence: 99%